The Effects of verbal and nonverbal Ostracism on employee interpersonal work behavior - Irshad, Muhammad; Arif, Dr. Muhammad; Hussain, Dr. Munir (The journal of contemporary issues in business and government, 2021)
Employee interpersonal behaviors play a vital role in the performance of any organization. If this behavior of the employee is positive it will boost up the performance of the organization otherwise it will completely lower the performance of the organization. The behavior of the employee is mainly affected by the behavior of other employees who are working with them. When a person or group of people fails to engage another organizational member when it is socially necessary to do so, it is referred to as workplace ostracism. There are two main dimensions of workplace ostracism which are verbal and nonverbal ostracism. The purpose of this study is to investigate the effect of verbal and nonverbal ostracism on employee interpersonal deviance behavior in the public sector organizations of Balochistan. This study also aims to examine the moderating role of social self-efficacy on the relationship between verbal and verbal ostracism and inter-personal deviance behavior. The nature of this study is quantitative so used the deductive approach. Primary data was collected by a closed-ended questionnaire from the 103 permanent employees of the public sector organization of Balochistan who speak a mother tongue other than the local language of that area. The data analysis technique was PLS-SEM done by the PLS Smart. From the results of this study it was found that both verbal and nonverbal ostracism will create a Disidentification in the employee which leads them to interpersonal deviance behavior. While social self-efficacy plays a moderation role in the relationship of verbal ostracism to interpersonal deviance behavior. There is no role of social self-efficacy in the relationship of nonverbal ostracism to interpersonal deviance behavior. It is recommended to the public sector organizations of Balochistan control the workplace ostracism behaviors especially verbal and nonverbal ostracism to make their employees more and more productive.